Regulating Mobility: Analyzing the Legal and Policy Framework for Mobile Street Vendors in Kalaburagi City (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper examines the legal and policy framework governing mobile street vendors in Kalaburagi City, Karnataka, with a focus on balancing their mobility with regulatory measures. Street vending is a critical economic activity for urban informal sectors, providing livelihood opportunities to a significant portion of the population. However, the mobility of these vendors often creates challenges related to urban planning, traffic congestion, public safety, and sanitation. The study analyzes the existing policies and laws at both local and national levels, such as the Street Vendors (Protection of Livelihood and Regulation of Street Vending) Act, 2014, and its implementation in Kalaburagi. Through a detailed review of municipal regulations, field interviews with vendors, and discussions with local authorities, the paper highlights gaps, challenges, and opportunities in the regulation of street vending. Furthermore, it explores the role of local governance in facilitating a balanced approach that ensures the protection of vendors’ rights while addressing urban mobility concerns. The paper offers policy recommendations for improving the legal framework, suggesting adaptive strategies that promote a sustainable and inclusive street vending ecosystem in Kalaburagi City.